Poly[aqua[μ2-1,4-bis(imidazol-1-ylmethyl)benzene-κ2N3:N3′](μ2-5-hydroxybenzene-1,3-dicarboxylato-κ4O1,O1′:O3,O3′)cadmium(II)], a twofold interpenetrated CdSO4-like metal–organic polymer - Zhou, Shi; Li, Chuan-Bi; Wang, Qing-Wei; Ng, Seik Weng (International Union of Crystallography, 2011)
In the title cadmium(II) complex, [Cd(C8H4O 5)(C14H14N4)(H2O)] n, the 5-hy-droxy-benzene-1,3-dicarboxyl-ate (5-OH-1,3-bdc) and 1,4-bis-(imidazol-1-ylmeth-yl)benzene (1,4,-bix) lig-ands bridge water-coordinated CdII atoms to generate a three-dimensional network. Two carboxyl-ate groups from different ligands function as O,O′-chelates, while two imidazole N atoms from different ligands coordinate in a monodentate fashion, and one water mol-ecule completes the seven-coordinate penta-gonal bipyramid around the CdII atom, in which the N atoms occupy the axial sites and the O atoms occupy the equatorial sites. The overall architecture is a twofold inter-penetrated CdSO4-type framework. The two crystallographically equivalent frameworks are linked by O-H⋯O hydrogen bonds between the water, hy-droxy and carboxyl-ate groups. © 2011 International Union of Crystallography.